Geographically based investigation of the influence of very-preterm births on routine mortality statistics from the UK and Australia. Issue 3 (4th October 2007) - Field, D; Bajuk, B; Manktelow, B N; Vincent, T; Dorling, J; Tarnow-Mordi, W; Draper, E S; Smart, D Henderson
Abstract : Background: Comparisons of national perinatal and neonatal mortality often neglect the underlying causes. Objective: To assess effects of very-preterm births in the UK and Australia. Setting: Two geographically defined populations: the former Trent Health Region of the UK and New South Wales (NSW)/the Australian Capital Territory (ACT), Australia. Method: All births 22 +0 to 31 +6 weeks in 2000, 2001 and 2002 were identified by established surveys of perinatal care. Rates of birth and death were compared. Results: The population of NSW/ACT was 35% higher and there were 66% more births than in Trent (273 495 vs 164 824). The proportion of liveborn infants between 22 and 31 weeks gestation was about 25% higher in Trent (NSW/ACT 2945, rate per 1000 live births 10.82 (95% CI 10.43 to 11.22); Trent 2208, rate per 1000 live births 13.47 (95% CI 12.92 to 14.05)). The proportion of these infants admitted to a neonatal unit was also higher in Trent (91.2% vs 94.4%; OR 1.63 (95% CI 1.30 to 2.05)). Unadjusted mortality in infants admitted to a neonatal unit was similar: NSW/ACT 332/2686 (12.4%); Trent 284/2085 (13.6%); unadjusted OR 1.12 (95% CI 0.94 to 1.33; p = 0.21). Conclusions: The higher rates of very premature birth and more ready admission to neonatal intensive care for infants in the UK may help to explain why perinatal and neonatal mortality are higher there than in Australia. Efforts to understand why the rate of premature birth in the UK is so high should be a national priority.